VALIDASI METODE ANALISIS ASAM LEMAK TRANS DALAM MAKANAN BERDASARKAN AOCS OFFICIAL METHOD Ce 1h-05 - Maria Fransisca Njoman; Nuri Andarwulan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Cardiovascular disease is related to the high consumption of trans fatty acid. This issue has driven SEAFAST IPB Laboratory to develop a trans fatty acid analysis method for gas chromatography based on AOCS Official Method Ce 1h-05. This research was aimed to validate the method via three steps: preparation step, procedure orientation test, and method validation. During instrument performance testing in the preparation step, linearity, limit of detection (LoD), limit of quantitation (LoQ), range, and precision parameters were validated for FAME 9t-C18:1 and C18:2 isomer mixed standard solution. During the method validation step, specificity, precision and accuracy parameters were validated for 9t-C18:1 compound attached to food matrix, i.e. doughnut. The instrument validation result of 9t-C18:1 standard solution had fulfilled the criteria of linearity (r2=1, requirement r2 > 0.990) within the range of 0.0020 to 0.1200 mg/mL; precision (RSD) 0.24%; LoD 0.0007 mg/mL and LoQ 0.0020 mg/mL. The instrument validation result for each isomer in C18:2 standard solution also met the criteria of linearity (r2= 0.9999, requirement r2 > 0.990) with precision (RSD), LoD and LoQ respectively; 1) 9t,12t-C18:2: 1.40%; 0.0033 mg/mL; 0.0100 mg/mL; 2) 9t,12c-C18:2: 1.89%; 0.0015 mg/mL; 0.0045 mg/mL; 3) 9c,12t-C18:2: 2.39%; 0.0015 mg/mL; 0.0044 mg/mL; 4) C18:2 cis: 3.39%; 0.0006 mg/mL; 0.0019 mg/mL. The validation result for 9t-C18:1 in 100 mg fat extract of doughnut suggested that the modified method is validated in term of specificity (Rs = 1.2), precision (RSD fatty acid content (mg/g) = 1.78%; RSD percentage of fatty acid content towards total fatty acid = 0.72%) and accuracy (as percentage of recovery) 80.54-94.25%.